Tradisi Keislaman Masyarakat Sunda pada Abad ke-19 - Purnama, Agung (Historia Madania: Jurnal Ilmu Sejarah, 2021)
This paper analyzes the religiosity of the Sundanese people in a historical approach, to be precise around the 19th century. The method used is the Historical Method which consists of heuristics, criticism, interpretation, and historiography stages. The results of the study show that the Sundanese people are known as religious people. Islam as a religion adopted by most of the Sundanese Tatar population has been acculturated with the local culture and with the noble values inherited by the Karuhun. In Sundanese society, Islamic teachings are often expressed with the taste of local traditions. Instead, local traditions are often given the breath of Islam, which further strengthens the religiosity of its adherents. In addition to carrying out the basic religious shari’ah, the religious expression of the Sundanese people is present in the form of religious holidays which are commemorated lively. Likewise, the stages of a person’s life, such as birth, childhood, marriage, until death, have religious and cultural instruments attached to them.